The Association of Adverse Perinatal Outcomes in Pregnancies with Gestational Diabetes and Excessive Gestational Weight Gain According to Obesity Status - Lesser, Henry; Movva, Vani; Young, Amanda; Gray, Celia; Mackeen, A Dhanya (American Journal of Perinatology, 2025)
Obesity, gestational diabetes mellitus (GDM), and excessive gestational weight gain (EGWG) are associated with adverse outcomes. It is unclear which carries the greatest risk. In this study, the relationship of obesity, GDM, and EGWG independently and concomitantly was analyzed to determine if one is a greater risk factor than the other.A retrospective cohort study of singleton gestations at Geisinger from October 2007 to March 2023 was performed. Exclusion criteria were pregravid body mass index (BMI) <18 kg/m2, gestational age (GA) <34 weeks, pregestational diabetes or chronic hypertension, prior cesarean delivery (CD) or contraindication to vaginal delivery. Patients were grouped by BMI class, and the order of groups within each BMI for the test for trend were no GDM/no EGWG, GDM/no EGWG, no GDM/EGWG, and GDM/EGWG. The rates of hypertensive disorders of pregnancy (HDP), severe HDP, CD, large for gestational age (LGA), shoulder dystocia, and neonatal intensive care unit (NICU) admission at ≥35 weeks were evaluated. A test for trend and odds ratios with 95% CIs were reported. p-values were reported across the GDM/EGWG groups per BMI category.A total of 42,627 pregnancies were included. At each BMI category, HDP, severe HDP, CD, LGA, and shoulder dystocia generally increased from patients with no GDM/no EGWG to those with GDM/no EGWG to those with no GDM/EGWG to those with GDM/EGWG. NICU admission at ≥35 weeks did not follow this progression.EGWG poses a greater risk than GDM regardless of pregravid BMI for HDP, severe HDP, CD, LGA, and shoulder dystocia. Attention should be given to determine the optimal strategy to manage pregnancies experiencing EGWG.
Keywords: excessive gestational weight gain; adverse perinatal outcomes; gestational diabetes; obesity